Multi-hazard performance-based design for multi-purpose structure in Isla Butig, Eastern Samar - Del Mundo, NC Augustine B.
This study aims to design a multi-purpose struture in Isla Butig, Easter Samar using the concepts of performance-based design. Performance-based is a part of disaster risk reduction management wherein the vulnerability a structure is minimize by designing the structure based on the target response of a possible hazard with alternative design that are not used in the typical practice in code-based design while keeping the cost to minimum. This way the structure will be reliable against a hazard and economical at the same time. Multi-hazard performance-based design considers the different design parameter that would affect beneficially and detrimentally the structure for each hazard. The damage response must fall within the target range provided by the acceptance criteria which are limits of the values of response of the structure for each hazard; if not redesigning the structure must be done. And even if the structure passes these accepted criterion, redesign is done to optimize the performance of the structure and reduce the overall cost of construction. A recommended structural design is provided that have conformed to the following criterions based on this study.